Virus Infections and Host Metabolism—Can We Manage the Interactions? - Sumbria, Deepak; Berber, Engin; Mathayan, Manikannan; Rouse, Barry T. (Frontiers in Immunology, 2021)
When viruses infect cells, they almost invariably cause metabolic changes in the infected cell as well as in several host cell types that react to the infection. Such metabolic changes provide potential targets for therapeutic approaches that could reduce the impact of infection. Several examples are discussed in this review, which include effects on energy metabolism, glutaminolysis and fatty acid metabolism. The response of the immune system also involves metabolic changes and manipulating these may change the outcome of infection. This could include changing the status of herpesviruses infections from productive to latency. The consequences of viral infections which include COVID-19, may also differ in patients with metabolic problems, such as diabetes mellitus (DM), obesity and endocrine diseases. Nutrition status may also affect the pattern of events following viral infection and examples that impact on the pattern of human and experimental animal viral diseases and the mechanisms involved are discussed. Finally, we discuss the so far few published reports that have manipulated metabolic events in-vivo to change the outcome of virus infection. The topic is expected to expand in relevance as an approach used alone or in combination with other therapies to shape the nature of virus induced diseases.